The Effect of Google Sites Web-Based Learning Media on Students' Science Learning Outcomes - Rosita Ningsih; Haryanto (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to reveal the effect of Google Sites Web-based learning media on student learning outcomes in science subjects of class X of SMK Negeri 1 Tana Tidung. This study is a quasi-experimental study targeting class X of SMK Negeri 1 Tana Tidung. The research respondents consisted of two groups, namely the experimental group and the control group with the same number of students, namely 11 students determined by the cluster random sampling technique. The data collection instrument was a test. The research data were obtained from the test results before and after learning. The data obtained were then analyzed using the Mann Whitney nonparametric test in the SPSS.16 program to see the differences between the experimental group and the control group. The results showed that there was a difference between the experimental group and the control group with a significance of 0.001 <0.05. These results conclude that there is an effect of Google Sites Web-based learning media on student learning outcomes in science subjects of class X of SMK Negeri 1 Tana Tidung.